Antigen structural requirements for recognition by a cyclobutane thymine dimer-specific monoclonal antibody. - Komatsu, Y (1997)
A monoclonal antibody (TDM-2) specific to a UV-induced cyclobutane pyrimidine dimer (T[cis-syn]T) has previously been established; however,the immunization had used UV-irradiated calf-thymus DNA containing a heterogeneous mixture of photoproduct sites. We investigated here the structural requirements of antigen recognition by the antibody using chemically synthesized antigen analogs. TDM-2 bound with cis-syn,but not trans-syn thymine dimer,and could bind strongly with four nucleotide analogs in which the cis-syn pyrimidine dimer was located in the center. Antigen analogs containing abasic linkers at the 5'- or 3'-side of the cis-syn cyclobutane pyrimidine dimer were synthesized and tested for binding to TDM-2. The results indicated that TDM-2 recognizes not only the cyclobutane ring but also both the 5'- and 3'-side nucleosides of the cyclobutane dimer. Furthermore,it was proved that either the 5'- or 3'-side phosphate group at a cyclobutane dimer site was absolutely required for the affinity to TDM-2. The antibody showed a strong binding to single stranded DNA but indicated little binding to double stranded DNA.